AFM advanced modes for dental and biomedical applications - Burgo, ThiagoA.L. [UNESP]; Pereira, Gabriel Kalil Rocha; Iglesias, Bernardo Almeida; Moreira, Kelly S.; Valandro, Luiz Felipe (Elsevier, 2022)
Several analytical methods have been employed to elucidate bonding mechanisms between dental hard tissues, luting agents and restorative materials. Atomic Force Microscopy (AFM) imaging that has been extensively used in materials science, but its full capabilities are poorly explored by dental research community. In fact, commonly used to obtain topographic images of different surfaces, it turns out that AFM is an underestimated technique considering that there are dozens of basic and advanced modes that are scarcely used to explain properties of biomaterials. Thus, this paper addresses the use of phase-contrast imaging, force-distance curves, nanomechanical and Kelvin probe force techniques during AFM analysis to explore topological, nanomechanical and electrical properties of Y-TZP samples modified by different surface treatments, which has been widely used to promote adhesive enhancements to such substrate. The AFM methods are capable of access erstwhile inaccessible properties of Y-TZP which allowed us to describe its adhesive properties correctly. Thus, AFM technique emerges as a key tool to investigate the complex nature of biomaterials and highlighting its inherent interdisciplinarity that can be successfully used for bridging fragmented disciplines such as solid-state physics, microbiology and dental sciences.
Keywords: Atomic force microscopy; Biomedical applications; Force-distance spectroscopy; Kelvin force; Phase-contrast; Tribochemistry